Selective Blocking of Graphene Defects Using Polyvinyl Alcohol through Hydrophilicity Difference - Kim, Yoon-jeong; Kim, Yang Hui; Ahn, Seokhoon (MDPI Open Access Publishing, 2023)
Defects on graphene over a micrometer in size were selectively blocked using polyvinyl alcohol through the formation of hydrogen bonding with defects. Because this hydrophilic PVA does not prefer to be located on the hydrophobic graphene surface, PVA selectively filled hydrophilic defects on graphene after the process of deposition through the solution. The mechanism of the selective deposition via hydrophilic-hydrophilic interactions was also supported by scanning tunneling microscopy and atomic force microscopy analysis of selective deposition of hydrophobic alkanes on hydrophobic graphene surface and observation of PVA initial growth at defect edges.